1991
DOI: 10.1126/science.1948054
|View full text |Cite
|
Sign up to set email alerts
|

The Anion Paradox in Sodium Taste Reception: Resolution by Voltage-Clamp Studies

Abstract: Sodium salts are potent taste stimuli, but their effectiveness is markedly dependent on the anion, with chloride yielding the greatest response. The cellular mechanisms that mediate this phenomenon are not known. This "anion paradox" has been resolved by considering the field potential that is generated by restricted electrodiffusion of the anion through paracellular shunts between taste-bud cells. Neural responses to sodium chloride, sodium acetate, and sodium gluconate were studied while the field potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
103
0
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(113 citation statements)
references
References 26 publications
(28 reference statements)
8
103
0
2
Order By: Relevance
“…In fact, this anion effect was so pronounced that despite having twice the number of cations in (NH 4 ) 2 SO 4 , responses were still less than those to NH 4 Cl. This pronounced anion effect was also apparent in K+ responses and ENaC-independent Na+ responses, consistent with our studies as well as others in rats (Elliott and Simon 1990;Ye et al 1991;Lundy and Contreras 1997;Breza and Contreras 2012b), and hamsters (Rehnberg et al 1993) demonstrating that the function of the ENaC-independent pathway for salts is a highly conserved mechanism across several species of rodents.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In fact, this anion effect was so pronounced that despite having twice the number of cations in (NH 4 ) 2 SO 4 , responses were still less than those to NH 4 Cl. This pronounced anion effect was also apparent in K+ responses and ENaC-independent Na+ responses, consistent with our studies as well as others in rats (Elliott and Simon 1990;Ye et al 1991;Lundy and Contreras 1997;Breza and Contreras 2012b), and hamsters (Rehnberg et al 1993) demonstrating that the function of the ENaC-independent pathway for salts is a highly conserved mechanism across several species of rodents.…”
Section: Discussionsupporting
confidence: 79%
“…We used 0.5 M sodium and potassium salts bound to 1 of 4 anions (chloride, acetate, sulfate, and gluconate), as well as 0.5 M CaCl 2 , MgCl 2 , NH 4 Cl, and (NH 4 ) 2 SO 4 . We used high salt concentrations so that we could analyze salt responses with large anions, which are known to suppress the nonselective pathway in rats (Ye et al 1991;Lundy and Contreras 1999;Breza and Contreras 2012b) and hamsters (Rehnberg et al 1993). Sodium chloride is the archetypal stimulus for saltiness and more highly preferred than the other salts.…”
Section: Chemical Stimuli and Solution Deliverymentioning
confidence: 99%
“…In fact, the amplitude of the rat chorda-tympani nerve response to sodium was progressively smaller as the size of the anion became larger (Beidler 1954;Elliott and Simon 1990;Ye et al 1991;. Rehnberg, et al (1993) showed that this "anion effect" may be a characteristic of the nonselective salt-sensing pathway.…”
mentioning
confidence: 99%
“…Three sodium salts with different sized anions were used to limit AI transduction (Elliot & Simon, 1990;Formaker & Hill, 1988;Kitada, Mitoh, & Hill, 1998;Ye et al, 1993). Sodium gluconate in particular was chosen on the basis of its ineffectiveness in stimulating AI transduction (Ye, Heck, & DeSimone, 1991;Ye et al, 1993). This experiment marks the first time to our knowledge that sodium gluconate has been presented to sodium-depleted rats.…”
mentioning
confidence: 99%